Innovative Approaches To Developing A Culture Of Professional Reflection In Future Teachers: Theoretical Basis And Experimental Analysis - Rozmetova Farangis Azamatovna (Academia One Publishing, 2025)
This study aims to develop the theoretical foundations of a methodology for developing a culture of professional reflection in future educators and to empirically verify its effectiveness. The research was conducted at Urgench State University in 2022-2025. 103 students of the "Preschool Education" department participated in the experimental work (experimental group - 48, control group - 55). Theoretical analysis revealed four main components of the culture of professional reflection (motivational-valuative, cognitive-knowledge, operational-activity, reflexive-evaluation) and their interrelationships. The developed theoretical model and methodology effectively develop the culture of professional reflection of future educators. The author's position is based on the synthesis of reflexive and innovative approaches, integration with practice, and systematic development.
Keywords: culture of professional reflection; future educators; innovative approaches